New Testament Philology: Essays in Honor of David Alan Black - Winstead, Melton Bennett (Wipf and Stock Publishers, 2018)
Intro -- Title Page -- Permissions -- List of Contributors -- Introduction -- Chapter 1: Who is Resisting-the Righteous One or Someone Else? -- Chapter 2: "Give Me This Water(!)" -- Chapter 3: Verbal Aspect and Imperatives -- Chapter 4: Semitic Wordplay Behind the Greek of the New Testament -- Chapter 5: An Overview of the Gnomic or Logical Future Tense in the Pauline Corpus -- Chapter 6: The Role of Chiasm for Understanding Christology in Hebrews 1:1-14* -- Chapter 7: The Virginal Conception -- Chapter 8: Is Relevance Theory Relevant for Biblical Studies? -- Chapter 9: Disarming Significant Textual Issues in Jude -- Chapter 10: The Linguistic Features of Second Timothy and Its Purpose -- Chapter 11: Scripture Memorization and Theological Education -- Chapter 12: Defining Discourse Analysis as an Important New Testament Interpretive Framework -- Chapter 13: Legal Metaphors in 2 Thessalonians 1 and 2 -- Chapter 14: "Participatory" Language in Ephesians Mediated through Σύν Compounds.